Plataforma de rehabilitación para lesión del manguito rotador basado en juegos serios utilizando un sistema de captura de movimiento (2021)
Therapies focused on the recovery of mobility in the shoulder are one of the most frequent causes of visiting the physiatrist; so much so that, in Colombia, it is estimated that 10% of medical consultations are related to some type of pathology in the shoulder. However, the success of the recovery depends on the perseverance and the correct application of the exercises postulated by the professional in physiotherapy. However, the partial rupture of the ligament in the rotator cuff is a type of injury that requires a considerable number of therapies (depending on the evolution of each patient), which induces the patient to drop out as satisfactory results are not found. its short-term evolution. This project is focused on implementing an alternative for the rehabilitation of shoulder injuries; based on serious games, which allow quantifying the evolution of the patient; for which an interaction tool or sensor (Kinect for XBOX ONE) was used, which allows to capture the movements of the joint (shoulder) of the patient; in order to identify the correct posture in each rehabilitation exercise and thus support the recovery process. Through the UNITY 3D development environment, the interaction platform is created which, together with the motion sensor, allows the measurement of kinematic parameters such as: speed, angular position and displacement; essential for checking the proper postures in each therapeutic exercise. In the same way, each procedure established in the game is guided and supervised by a professional in physiotherapy, who establishes the type of exercise according to the characteristics of an injury or pathology and verifies the movements of flexion, extension, abduction and adduction, performed by the patient. 15 Finally, tests are carried out for the validation of the platform, where a series of sessions is created in which it treats 14 patients diagnosed with tendonitis in the shoulder: “partial rupture of tendons in the shoulder”. Each session is supervised and advised by the physiotherapy professional, while the platform quantifies the kinematic parameters resulting from the exercises developed by the patient during the session. In the first session, the initial parameters of each patient are created, identifying the velocity, the angular position and the displacement of the forearm, for the movements of flexion, extension, abduction and adduction. During the next three sessions, the patient is asked to follow the arm movements indicated in the game, while these parameters are captured and progress is evaluated session after session.